114 Treatment of Bifurcation Aneurysms Using Single Stent-Coiling With Relation to Aneurysm Configuration: A Cohort Study of Two Academic Institutions in the United States. (August 2016) - Adeeb, Nimer; Patel, Apar S.; Griessenauer, Christoph Johannes; Moore, Justin M.; Foreman, Paul M.; Gupta, Raghav; Harrigan, Mark R.; Ogilvy, Christopher S.; Thomas, Ajith J.
Abstract : INTRODUCTION: Stent-coiling of bifurcation aneurysms has significantly expanded the spectrum of aneurysms amenable to endovascular therapy. A variety of techniques have evolved to deal with wide-necked bifurcation aneurysms such as Y-stenting and WEB embolization device. In our 2 institutions, we have primarily used a single stent coiling to treat most bifurcation aneurysms. We present a large series in which a single stent was utilized with angiographic and clinical outcomes. METHODS: Two academic institutions in the United States contributed prospectively maintained data on consecutive patients with bifurcation aneurysms treated with single stent coiling between 2007 and 2015. RESULTS: A total of 58 bifurcation aneurysms were treated with single stent coiling at the 2 institutions. The aneurysms were located in the basilar bifurcation in 51.7%, carotid bifurcation in 24.1%, middle cerebral artery bifurcation in 19%, and anterior communicating artery bifurcation in 5.2%. The median aneurysm diameter, neck size, height, width, and aspect ratio were 8.4, 6, 7.5, 7.4, and 1.5 mm, respectively. Median length of follow-up was 16.5 months. Complete occlusion at last follow-up was achieved in 70.6% of cases, residual neck was found in 21.6%, and residual aneurysm was found in 7.8%. Re-treatment was needed in 12.1% of cases due to recanalization. There was a significant association between complete occlusion and smaller neck size (notably <6 mm; P = .036) and smaller width (notably <7.5 mm; P = .022). Furthermore, complete occlusion rate was lower in basilar bifurcation aneurysms ( P = .088) and in large bifurcating angle (notably >180°; P = .034). Symptomatic complications occurred in 6.9% of cases. There was no mortality. CONCLUSION: Treatment of bifurcation aneurysm using single stent-coiling is considered safe and effective. Complete and near-complete occlusion were achieved in 92.2% of cases. Residual aneurysm or recanalization was found only in 7.8% of cases. Therefore, the use of Y-stenting or other devices can be limited to a subset of basilar bifurcation aneurysms, with aneurysm neck wider than 7 mm and/or those with a bifurcation angle greater than 180°.